Thinking Beyond the Temporal Bone Lab: A Systematic Process for Expanding Surgical Simulation in Otolaryngology Training. (July 2023) - James, Joel; Irace, Alexandria L.; A. Drusin, Madeleine; Kim, Ana H.; Gudis, David A.; Overdevest, Jonathan B.
The COVID-19 pandemic led to a temporary lapse in the development of otolaryngology trainee operative skills due to the cancellation of elective procedures and redeployment of trainees and attendings to COVID-19 units. Although transient, this disruption provided an opportunity for otolaryngology programs to develop contingency plans and formalize nascent simulation training curricula. Integration of formal simulation training alongside current didactic and surgical education may offset lost exposure during surgically lean times while providing the framework and resources for enhanced baseline training. Here, we provide an up-to-date overview of surgical simulation models in otolaryngology and identify easily implementable, low-cost, low fidelity models for junior trainees. By taking advantage of rapid advancements in technology and a paradigm shift to a more hands-on approach in medical education, formal simulation training may prove to be a beneficial tool at all stages of residency training, allowing for expanded peer-mentored skill development and providing a safe haven during unforeseen disruptions in surgical case volume.